2009
DOI: 10.1175/2009mwr2922.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Large-Scale Environments of Moderate and Intense Precipitating Systems in the Mediterranean Region

Abstract: International audienceA characterization of the large-scale environment associated with precipitating systems in the Mediterranean region, based mainly on NOAA-16 Advanced Microwave Sounding Unit (AMSU) observations from 2001 to 2007, is presented. Channels 5, 7, and 8 of AMSU-A are used to identify upper-level features, while a simple and tractable method, based on combinations of channels 3-5 of AMSU-B and insensitive to land-sea contrast, was used to identify precipitation. Rain occurrence is widespread ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 66 publications
(74 reference statements)
11
62
0
Order By: Relevance
“…Summer electrical activity is predominately located over continental Europe while during the winter the electrical convective clouds are mainly observed over the Mediterranean Sea, as established by climatology based on lightning records (e.g., Holt et al, 2001;Christian et al, 2003;Defer et al, 2005) or on space-based microwave measurements (e.g., Funatsu et al, 2009). Holt et al (2001) Adamo (2004) reported that the flash rates over the Mediterranean Sea are significantly smaller than those recorded at similar latitudes in the United States.…”
Section: The Peach Experimentsmentioning
confidence: 96%
“…Summer electrical activity is predominately located over continental Europe while during the winter the electrical convective clouds are mainly observed over the Mediterranean Sea, as established by climatology based on lightning records (e.g., Holt et al, 2001;Christian et al, 2003;Defer et al, 2005) or on space-based microwave measurements (e.g., Funatsu et al, 2009). Holt et al (2001) Adamo (2004) reported that the flash rates over the Mediterranean Sea are significantly smaller than those recorded at similar latitudes in the United States.…”
Section: The Peach Experimentsmentioning
confidence: 96%
“…Its geographical location between the Subtropics and the midlatitudes, the complex orography surrounding the Mediterranean Sea, and the large reservoir of sometimes warm water contribute to the formation of a broad continuum of cyclones, from shallow, warmcore to deep, cold-core storms (Campins et al, 2006). Satellite observations show a majority of cloud systems at the mesoscale, only a fraction being associated with an upper-level anomaly and preferentially during the cold season (Chaboureau and Claud, 2006), while deep convection has been sensed over the sea mostly during autumn (Funatsu et al, 2009). Among the Mediterranean cyclones accompanied by upper-level anomalies and deep convection, about 15 mesocyclones have been observed over the last 20 years, preferentially in autumn (Fita et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The Italian and Balkan peninsulas are affected by moisture originating in the MB. In a similar study, Gomez-Hernandez et al (2013) pointed out the west Mediterranean Sea as the dominant moisture source for most MB regions during the wet season.…”
Section: Moisture Sourcesmentioning
confidence: 85%
“…An investigation of the link between atmospheric circulation patterns and Iberian total rainfall for the period 1958-1997 led by Goodess and Jones (2002) revealed that the NAO negative mode produces high-pressure blocking in the northeast Atlantic, and a more meridional circulation than the opposite, NAO positive mode, consistent with Moses et al (1987). Moreover, upper-air troughs and incursions of polar air over the Mediterranean are more frequent and the Atlantic storm tracks are displaced south.…”
Section: Mechanisms Governing Total and Extreme Rainfall Variabilitymentioning
confidence: 96%
See 1 more Smart Citation